2008
DOI: 10.1152/jn.90424.2008
|View full text |Cite
|
Sign up to set email alerts
|

Development of Theta Rhythmicity in Entorhinal Stellate Cells of the Juvenile Rat

Abstract: . Mature stellate cells of the rat medial entorhinal cortex (EC), layer II, exhibit subthreshold membrane potential oscillations (MPOs) at theta frequencies (4 -12 Hz) in vitro. We find that MPOs appear between postnatal days 14 (P14) and 18 (P18) but show little further change by day 28ϩ (P28 -P32). To identify the factors responsible, we examined the electrical responses of developing stellate cells, paying attention to two currents thought necessary for mature oscillation: the h current I h , which provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 79 publications
(133 reference statements)
2
37
0
Order By: Relevance
“…It is therefore interesting that Burton et al (2008) found a continuous increase in the expression of HCN channels up to the end of their study at P28, although they did not find a clear physiological correlate of this process. This pattern agrees with data by Richter et al (1997) and with our own findings showing age-related acceleration of the sag potential.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is therefore interesting that Burton et al (2008) found a continuous increase in the expression of HCN channels up to the end of their study at P28, although they did not find a clear physiological correlate of this process. This pattern agrees with data by Richter et al (1997) and with our own findings showing age-related acceleration of the sag potential.…”
Section: Discussionmentioning
confidence: 87%
“…It is usually difficult to dissociate the effects of sensory experience and genetically prescribed patterns of postnatal maturation. Burton et al (2008) found that dendritic spine density of mEC layer II stellate cells increased almost threefold from the second to the fourth postnatal week without changes of stellate cell excitability beyond P18. However, as our data show, the intrinsic excitability continues to change differentially within the population.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We have demonstrated that presynaptic stimulation at 5 Hz within the theta frequency (4--12 Hz) induces depression of glutamatergic transmission via activation of mGluR II. Theta oscillations are associated with memory (Buzsaki 2002(Buzsaki , 2005Hasselmo 2006) and are found in the EC (Alonso and Llinas 1989;Burton et al 2008). Whether mGluR II--mediated depression of glutamate release plays a role in mGluR II--mediated modulation of memory still remains to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Single neuron models used the framework developed by Izhikevich (2007) with the following equations: Cv.=k(vvr)(vvt)u+(Ib+I)u.=a{b(vvr)u} where v is the membrane potential, u is the current, I b is the baseline holding current, I is the injected current, C is the membrane capacitance (pF), v r is the resting membrane potential (mV), v t is the threshold voltage, k is the fast activation current with a , the fast current and b , the slow current, v peak is the maximum voltage of a spike, c is the reset voltage, and d is the reset current. Parameters were chosen to match previously published values (Izhikevich, 2007) used to replicate properties of stellate cell recordings in mEC (Burton, Economo, Lee, & White, 2008). For all simulations we used the following parameter values: I b = 130, C = 200, v r = −60, v t = −45, k = 0.75, a = 0.007 for low frequency resonance, a = 0.015 for high frequency resonance, b = 14.2, c = −50, d = 100, and v peak = 100.…”
Section: Methodsmentioning
confidence: 99%